Open source software in small libraries: Myths and realities - Awang Abu Bakar, Normi Sham; Mansor, Yushiana (2014)
Open source softwares provide great opportunities for the sharing libraries and information centres. This paper demonstrates the applications of Koha and DSpace at the Hamzah Fansuri Resource Centre, at the Kulliyyah of ICT, IIUM. The successful implementations of both softwares exemplify how small libraries can deploy open source solutions to enhance the delivery of information services. Several misconceptions have been found to delay the decision of small libraries in automating their libraries. This paper seeks to uncover some myths about open source softwares as gathered from individuals managing small libraries. With proper palnning and administration, adoption of open source softwares in small libraries could enhance the role of libraries in society and strengthen cooperation among libraries in the Muslim world.